Myeloproliferative Disease: Dealing With a Diagnostic Dilemma - Devkota, Khagendra Raj; Subedi, S; Bhandari, S; Kandel, B; Shrestha, J; Sharma, KS (Nepalese Journal of Cancer, 2021)
Myeloproliferative neoplasms (MPNs) constitute a group of hematologic clonal diseases that affect one or more myeloid lineages with abnormal proliferation. It is rare disease entity and incidence is about 1.15 to 4.99/100 000 person-years among hematological neoplasms for all subtypes of MPNs combined. Patients who present with hepatosplenomegaly, hyperleukocytosis with monocytosis should have routine tests along with bone marrow morphology possibly biopsy, quantiferon TB Gold in tube test, Dengue fever IgM, IgG, NS-1 antigen, cytogenetics t(9;22), BCR cABL fusion gene, JAK-2 V617F, MPL mutations, CALR gene test done along with karyotyping and flowcytometry to evaluate and establish diagnosis towards management.